Hardscape floristics: Functional and phylogenetic diversity of parking‐lot plants. Issue 4 (25th September 2019) - Frazee, Lauren J.; Aronson, Myla F. J.; Kattge, Jens; Struwe, Lena
Abstract: Questions: The study of organisms living in extreme environments has shaped our knowledge of the deterministic and stochastic factors that contribute to community assembly. With hardscape habitats (HH), humans have created a novel land‐cover type that is physically analogous to extreme terrestrial environments such as deserts, barrens, and rocky outcrops and may harbor rare or specialist species and communities. We addressed the following questions: (a) which plant species inhabit hardscapes; (b) do hardscapes serve as a refuge for rare or specialist species; (c) how taxonomically similar are hardscape plant communities to one another and the regional species pool; (d) is phylogenetic diversity of hardscape communities different from that of the regional species pool; and (e) which functional traits and life history strategies are filtered for or against in hardscape plant communities? Location and Methods: We surveyed the vascular plant communities of 17 asphalt parking lots in New Jersey, USA, to use as a focal hardscape habitat for this study. Results: Parking‐lot plant communities contained 119 vascular plant taxa out of the 2, 199 regional species and had a lower beta and phylogenetic diversity than the regional species pool. The parking‐lot flora had significantly higher frequencies of annuals, biennials, C4 plants, ruderal strategists, non‐natives, herbaceous plants, self‐compatible species, and species from the Caryophyllales, Asterales, Ulmaceae, and Plantaginaceae clades compared to the regional pool and contained no New Jersey threatened or endangered species. Conclusions: Hardscape habitats may be similar to naturally occurring, extreme terrestrial environments in that they impose stringent filters on ecological communities leading to increased proportions of short‐lived and C4 plant species compared to the regional pool. Nevertheless, hardscapes are unlikely to serve as biodiversity refuges in the Northeastern USA as they create novel abiotic conditions that may be hostile to many native, rare, and specialist species. Abstract : We may be observing the formation of a new vegetation type — the temperate asphalt flora — due to the selective properties of asphalt in urban and suburban habitats. Hardscapes may not support floristic communities that are ecologically analogous to those of natural, extreme terrestrial environments but rather floras that reflect filtering mechanisms associated with anthropogenic preferences and norms.